Understanding Occupational Health and Safety Regulations and the Influence on Students' Behavior in Practical Workshops - Yusuf, M.; Suarbawa, I Ketut Gde Juli; Dewi, Ni Wayan Merda Surya; Sadiyani, Ni Wayan; Sudana, I Made (UI Scholars Hub, 2025)
Understanding occupational health and safety (OHS) is essential for engineering students, especially in high-risk environments such as mechanical workshops, where unsafe practices can lead to accidents and injuries. Although Regulation Number 5 of 2018 from the Indonesian Ministry of Manpower mandates OHS implementation in all workplaces, students’ knowledge and behavior still fall short of the expected safety standards. This study aimed to measure students’ understanding of OHS, their basic knowledge of OHS law, and their behavior during workshop practicum activities. A cross-sectional research design was used, involving 203 students in State Polytechnic in Badung District, Indonesia. Data were collected through direct observation, surveys, and interviews. OHS understanding and legal knowledge were assessed using a test questionnaire, while OHS behavior was evaluated using a Likert-scale-based questionnaire. Data were analyzed using structural equation modeling at a 95% confidence level. The results indicated that combined OHS understanding and legal knowledge influence OHS behavior by 25.1%, with legal knowledge alone contributing only 1.8%, suggesting that knowledge of the law cannot shape behavior independently. Other contributing factors, such as engaging teaching methods and continuous monitoring, are needed.